2010
DOI: 10.1063/1.3360937
|View full text |Cite
|
Sign up to set email alerts
|

Many-body design of highly strained GaInNAs electroabsorption modulators on GaInAs ternary substrates

Abstract: Electroabsorption in highly strained GaInAs and GaInNAs quantum wells (QWs) grown on GaInAs or quasi-GaInAs substrates is investigated by using microscopic many-body theory. The effects of various parameters, such as strain, barrier height, substrate composition, and temperature are thoroughly examined. It is shown that the value of the absorption coefficient strongly depends on the depth of the QWs under large bias electric field due to the small overlap integral of wave functions between the conduction and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although FCT is easy to use for obtaining optical properties of QWs, it needs an experimental fitting parameter (relaxation time) associated with optical spectrum broadening originating from scattering phenomena in semiconductors. Results obtained by FCT are greatly affected by the fitting parameter (shown later), and it was demonstrated that spectral positions and the spectral shapes obtained by FCT are not consistent with the experiment [10][11][12][13][14]. Therefore, it is difficult to grasp the inherent optical properties of GeSn QWs if FCT is used for the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FCT is easy to use for obtaining optical properties of QWs, it needs an experimental fitting parameter (relaxation time) associated with optical spectrum broadening originating from scattering phenomena in semiconductors. Results obtained by FCT are greatly affected by the fitting parameter (shown later), and it was demonstrated that spectral positions and the spectral shapes obtained by FCT are not consistent with the experiment [10][11][12][13][14]. Therefore, it is difficult to grasp the inherent optical properties of GeSn QWs if FCT is used for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the material gain of GeSn/SiGeSn QWs is investigated for mid-IR Si-photonics light sources by using microscopic many-body theory (MBT) [10][11][12][13][14][15]. MBT does not need any fitting parameters used in FCT to obtain optical properties of QWs and only needs basic bulk band parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the QCSE, it is important to use deep well (large band offset), especially for conduction band. A deep well makes the confinement of electron and hole stronger, leading to larger absorption even when the electric field is applied [15]. Therefore, to design the GeSn/SiGeSn QWs for EAM, the QW structure having large band offset has to be investigated first to use QCSE effectively.…”
Section: Qcse Of Gesn/sigesn Quantum Wellsmentioning
confidence: 99%